Evaluation of tactical performance in invasion team sports: a systematic review - Ávila-Moreno, F. M.; Chirosa-Rios, L. J.; Ureña-Espá, A.; Lozano-Jarque, D.; Ulloa-Diaz, D. (International Journal of Performance Analysis in Sport, 2018)
The objectives of this revision were to identify game indicators, the references for evaluating tactical efficiency, and the types of data analysis used in invasion team sports for the analysis of tactical performance. A search of the principal electronic databases was carried out, the procedure was adjusted to the PRISMA-P 2015 protocol, and 62 non-experimental published articles were obtained from the years 2000-2016. The results showed the complimentary use of diverse types of indicators and the frequent elaboration of instruments ad hoc. The individual technical-tactical actions were widely used. The record of standardised team actions was scarce. The research lines with a sequential data record for their temporary analysis were significant. The transitory or final score and the results of game sequences were the most used references of performance. The big data tools of analysis, web analysis, and the detection of temporal patterns or the application of polar coordinates were emerging methods of analysis.